Alternativas de plantas de tratamiento de aguas residuales municipales (PTARM) para ciudades con población menor o igual a 20.000 habitantes (2013)
This article evaluates and compares 4 wastewater treatment plants for municipalities with a population of ≤ 20,000 inhabitants design to provide criteria of selection in terms of convenience from the technical point of view. The treatment technologies selected for evaluation are 1) anaerobic lagoon + facultative pond, 2) facultative ponds in series, 3) activated sludge type ectended aeration and 4) UASB reactor + post-treatment with facultative pond. The results of the evaluation show that, in general, the most appropiate alternative of treatment is serially facultative ponds.